ANALISIS SEMIOTIK PADA IKLAN-IKLAN AQUA DI MEDIA TELEVISI - Puteri, Bunga Diantirta Yapati (Universitas Negeri Surabaya, 2017)
The analysis of this paper is related to the myth analysis of the adevertisements of Aqua water drink that are advertised in the television. Relating to this, these myth of Aqua has sent the messages to the readers? mind. These myth can the readers? mind to choose something and make a decision. In those advertisements of Aqua, the myth are sent by considering the location of video advertisement, colors choosing, ornamemts adding, time settings, choosing of musics, the characters of actors or actress, the compny image, and choosing of sentences that can persuade the readers to buy the Aqua product and specfifically make this myth becomes one of factors of influencein buying something. This analysis uses the library study to know and to observe the phenomena or conditions in producing the video advertisement of the water drink product. For this, the qualitative data are used to know the description of the myth of the product advertised and its supporting factors. The descriptive qualitative analysis is applied to analyse these data. The result of research proves that the majority of myth that involved in the advertisement can mention Aqua is the best hygiene water drink the people consume. These advertisements of Aqua can make the audiences or people believe that Aqua is the right water drink for the body health, especially in reducing dehydration and increasing the concentration of the person that consumes it.